PERENCANAAN PERAWATAN MESIN PENCACAH KAPAS BOR WASTE OPENER DENGAN METODE ISMO: MAINTENANCE PLANNING OF BOR WASTE OPENER COTTON CRUSHING MACHINE USING ISMO METHOD - Galang, Galang Bakti Nusa (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2022)
Cotton chopping machine Type Bor Waste Opener is one of the equipment used for production activities at PT Lotus Indah Textile Industries Cotton chopping machine Type The Bor Waste Opener must work properly and in a ready to use condition so that production activities are not hampered, so planned maintenance is needed. The purpose of this final report is to find out how to evercome the damage that often occurs in the Bo-r Waste Opener type cotton chopper, to plan activities and schedule machine maintenance using the ISMO method Implementation methods include collecting data by observation, interviews, and literature studies, as well as made maintenance plans using the ISMO method which included determining the degree of complexity, determining the maintenance cycle, designing maintenance activities, making maintenance schedules, and estimating maintenance and repair costs The results of this final report Problems that often occur in the Bo-r Waste Opener type are Finned strippe roll fins the fins are worn out due to frequent friction, spike lances in the form of the surface of the nails on the board coming off Results of planning activities for cotton chopper machine maintenance Type Bo-r Waste Opener using the ISMO method obtained data with a degree of complexity of 75 so that repair complexity 18 was obtained. Maintenance activities include 9 inspection activities, 6 small repair activities, 2 medium repair activities, and 1 Overhou! Calculation of the maintenance and repair planning obtained an estimated cost for the period 2023 to 2026 of Rp 3,614,367